Ventricular bigeminy and trigeminy caused by hypophosphataemia during diabetic ketoacidosis treatment: a case report - Miszczuk, Konrad (Ital J Pediatr, 2019)
BACKGROUND: Hypophosphatemia has many causes, and is often encountered during DKA (Diabetic Ketoacidosis) treatment. However, it rarely requires clinical intervention. CASE PRESENTATION: Ventricular arrhythmia was observed in a 10-year-old girl with newly diagnosed type 1 diabetes mellitus and hypophosphatemia while undergoing treatment for ketoacidosis. Oral phosphate supplementation ceased ventricular arrhythmia almost completely. CONCLUSIONS: The clinical signs of hypophosphatemia are potentially life-threatening. Therefore, physicians should be vigilant when treating patients who are at risk of hypophosphatemia. Severe hypophosphatemia accompanied by clinical symptoms requires oral or intravenous supplementation of phosphate.